PRODUCING PROBIOTIC CHEESE FROM SHEEP MILK BY USING PROBIOTIC BACTERIA - Maha Yousif (Mesopotamia Journal of Agriculture)
This study aimed to produce probiotic (Arabic cheese) by using a mixture of probiotic bacteria namely; Lactobacillus acidophilus andBifidobacteriumlongum. The cheese samples were made from sheep milk.  Control cheese was made with rennet only, while the probiotic cheese was made with a combination of probiotic bacterial strains in addition to the rennet. The produced cheese were analyzed chemically, microbiologically, and organoleptically at intervals (fresh, 7, 14, 21, and 28 days) at 4 c  in refrigerator. The results of the study revealed, a decrease in moisture content, pH, and total protein percentand an increase in fat, acidity, and soluble nitrogen percentages with the increase in storage periods for both kinds of cheese (the control and probioticcheese). The counts of Lb. acidophilus and Bif. Lognum were kept more than 106 during the storage and at the end of the storage. The probiotic cheese and the control had high scores of organoleptic properties. The results indicated that, the produced cheese (Arabic cheese) which contained both strains of probiotic bacteria offers another way in using dairy products as functional food.